Does the Balassa-Samuelson Theory Explain the Link Between Relative Population Growth and Purchasing Power Parity? - Hassan, A.; Salim, Ruhul (Economic Society of Singapore, 2013)
Relative population growth affects relative prices through the so-called Balassa–Samuelson (BS) mechanism and that in turn impacts PPP. This paper empirically investigates the relationship between the PPP exchange rate and relative population growth in a panel of 80 selected countries. Following the BS hypothesis, this paper argues that relative population growth affects nominal wages that impact price levels and thereby impacts PPP. Using panel cointegration and fully modified ordinary least square (FMOLS), the empirical results show that there is a stable relationship between PPP exchange rate and relative population growth in the long run. These empirical findings suggest that population growth have an important role in exchange rate determination through PPP.